Hydraulic modelling : an introduction : principles, methods and applications - Novák, Pavel, 1918- (London ; New York : Spon, 2010)
Presents a synthesis between classical physical models and the extensive range of constantly evolving computational techniques. This title shows how to pick the right model and to appreciate its strengths and limitations.
Introduction -- Theoretical background : mathematics -- Numerical techniques used in hydraulic modelling -- Theoretical background : hydraulics -- Development of physical models -- Tools and procedures -- Modelling of open-channel systems -- Environmental modelling of open-channel systems -- Modelling of closed-conduit flow -- Modelling of urban drainage systems -- Modelling of estuaries -- Modelling of coastal and nearshore structures and processes -- Modelling of hydraulic structures.
Includes bibliographical references (pages 581-585) and indexes.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Hydraulic engineering -- Data processing; Hydrodynamics -- Mathematics; Hydraulic structures -- Mathematical models; Electronic books